A case of synchronous malignant tumours in a parotid gland. (23rd June 2022) - Hankinson, Paul Michael; Karbhari, Bhavesh; Allsobrook, Olive; Nusrath, Muzzammil; Khurram, Syed Ali
Abstract: Synchronous unilateral tumours within the parotid gland of differing histological type are rare, accounting for less than 1% of parotid gland neoplasms. Here we present a case of a primary tumour of the parotid gland alongside a synchronous metastasis at the same site, highlighting the diagnostic and treatment challenges present, especially where a core biopsy is unable to sample the multiple tumour types. Though rare multiple tumour types must be kept in the differential diagnosis of multifocal salivary gland disease.